Energy subsidy reform for growth and equity in Egypt: The approach matters - Breisinger, Clemens; Mukashov, Askar; Raouf, Mariam; Wiebelt, Manfred (Elsevier, 2019)
Phasing out energy subsidies is high on the agenda of policymakers in several Middle Eastern and North African countries. The impact of such reform can vary widely depending on the country and policy. This paper contributes to the existing literature by examining the phasing out of energy subsidies in Egypt under alternative economic scenarios. In particular, we consider Egypt's short- and long-term economic adjustment under different assumptions on labor market flexibility, spending options of subsidy savings, and alternative social protection measures. Results from economy-wide model simulations suggest that energy subsidy cuts may hamper economic growth in the short term, but depending on the policy measure, will improve growth perspectives and household welfare in the longer term. Yet, findings also point to likely adverse impacts of the reform on household consumption in the short and longer run. To counteract such negative impacts, targeted social protection measures should be continued and scaled up in parallel with the phasing out of energy subsidies.